Now that kindergarten is free of charge: laying the foundations for future pre-school policy change in Bulgaria - Volen, Eugenia (Frontiers in Education, 2023)
Since April 1, 2022, all children in Bulgaria attend nursery and kindergarten completely free of charge. This paper makes the argument that without improving the quality of kindergarten services, policy gains toward expanding access remain fragile. The public early education system will continue to be challenged to realize the full potential of its impact. Strengthening demand for high quality kindergartens could bolster efforts to enhance the supply of such services. This could be achieved by reframing the role of kindergartens to society, improving the capacity of parents to voice their demands, and creating opportunities for them to do so. Moreover, civil society could encourage the establishment and communication to the public of process quality measurement in an effort to secure a broad foundation of support for greater investment in early education.